Antibacterial Activity of Patch Silver Nanoparticles and Chitosan with Cellulose Nanofibers Carriers against Staphylococcus aureus and Escherichia coli - Prayoga, Andre; Hasibuan, Poppy Anjelisa Zaitun; Yuandani (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
One of the medical needs whose demand continues to increase is wound dressings. The wound cover must also be non-toxic, non-allergenic, made of widely available biomaterials, and have antibacterial properties that can prevent infection of the wound. Chitosan is known to have wound healing activity by acting as a blood-clotting agent and stimulating the formation of new tissue, and silver nanoparticles have good antibacterial activity. Silver Nanoparticles and Chitosan with Cellulose Nanofibers carriers (SNCCN) are made in the form of patches with the ratio formula between cellulose nanofibers and chitosan/silver nanoparticles is 1:9, 2:8, 3:8, 4:7, 5:5, 6:4, 7:3, 8:2, 9:1, and 10:0. Then the antibacterial activity was tested against Staphylococcus aureus and Escherichia coli to find the best formula for antibacterial activity. The analysis showed that the SNCCN patch with a ratio of 9:1 had the best antibacterial activity against Staphylococcus aureus (13.8Â±0.05 mm) and Escherichia coli (12.5Â±0.05 mm). It can be concluded that patch Silver Nanoparticles and Chitosan with Cellulose Nanofibers carriers (SNCCN) have good antibacterial activity at a concentration of 9:1 in the category of strong inhibition (10-20 mm).